Management of Supply Chain Process for Meat Products - Nusran, Muhammad; Alam, Roslina; Triana, Dien; Parakkasi, Idris; Abdullah, Tajuddin (Indonesian Journal of Halal Research, 2019)
The purpose of this research plan is to make a mapping of the Halal Critical Point of Beef Products and a number of Processed Beef Products and also to create a Supply Chain Process Flow System for Meat products. Data and analysis of data explored in this research plan are stakeholders in the halal supply chain, namely authority institutions such as slaughtering houses (RPH), producers, logistics providers, operators, consumers, and the government by making questionnaires to identify criteria and sub-criteria important. The survey discusses consumer perceptions of the halal supply chain of products of beef and processed beef using the score method. The results of data processing can then be analyzed using the Analytical Hierarchy Process (AHP) model. This study is expected to contribute to the selection of important criteria for halal supply chains of Meat products and their processed products, then contribute to the priority index using AHP (Analytic Hierarchy Process)